The Lipide-Soluble Vitamin Contents of Some Lathyrus L. Species - Bahşi, Muammer; Emre, İrfan; Genç, Hasan Hakan; Şahin, Ahmet Anıl; Ökkeş,; Yılmaz, Okkes; Yilmaz, (My University, 2019)
In the present study, lipide-soluble vitamin contents in the seeds of the Lathyrus L. taxa (Lathyrus sylvestris L.,Lathyrus sphaericus Retz.; Lathyrus pratensis L., L. aphaca L. var. modestus P.H., L. aphaca L. var. biflorus Post.,L. aphaca var. pseudoaphaca (Boiss.) P.H. Davis, Lathyrus odoratus L., Lathyrus hierosolymitanus Boiss.,Lathyrus tauricola P.H. Davis) were determined by using HPLC. Data obtained from present study showed thatstudied Lathyrus taxa have high beta-caroten content (146,5±1,73-375,0±3,35 µg/g). present study found thatLathyrus pratensis has the higesht gamma-tocopherol content (158,9±3,65 µg/g) whilst L. aphaca var.pseudoaphaca (Boiss.) P.H. Davis has highest D3 vitamin content (43,2±2,18 µg/g) among studied taxa. However,it was found that the r-tocopherol, a-tocopherol, a-tocopherol acetate, retinol, retinol acetate, D2 and K1 vitaminsof studied Lathyrus taxa were lowest.
Keywords: Biyoloji